Effect of plyometric training on strength, vertical jump, flexibility, and range of motion in volleyball players - Messner, B.; Guyer, S.; Holder, J.; Skelton, M. (Medicine & Science in Sports & Exercise, 1999)
Female Division I volleyball players (N = 9) participated in a post-season plyometric training program twice a week for eight weeks.